Transition metal doped vanadium manganese sodium phosphate composite material as well as preparation method and application thereof
By doping Zr elements in sodium manganese vanadium phosphate material and carbon coating, the V-position doping amount is regulated, and the problems of poor conductivity and structural instability of the positive electrode material of sodium ion battery are solved, achieving high rate performance and long cycle life improves electrochemical performance.
Patent Information
- Application Number
- CN202411631485.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-15
- Publication Date
- 2025-02-14
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
The existing sodium ion battery positive electrode material Na4MnV (PO4)3/C has problems with poor conductivity and unstable structural conditions, which limits its rate performance and cycle life.
By doping the transition metal element Zr in the sodium manganese vanadium phosphate material, the Na4-xV1-xMnMx(PO4)3@C composite material is formed, and the V-position doping amount is regulated, the electronic conductivity of the material is improved and Structural stability.
The high rate performance and long cycle life of the material are achieved, and the electrochemical performance of sodium ion batteries is improved.
Smart Images

Figure CN119447255A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to a novel positive electrode material for a sodium ion battery, in particular to a transition metal-doped sodium manganese vanadium phosphate micron sphere nanomaterial and a preparation method and application thereof. Background Art
[0002] With the rapid development of renewable energy, the demand for large-scale energy storage systems is becoming increasingly urgent. Sodium-ion batteries are considered to be one of the most promising candidates for large-scale energy storage systems due to their advantages such as abundant raw materials and low cost. At present, layered transition metal oxides, Prussian blue analogs and polyanion compounds are the most common positive electrode materials for sodium-ion batteries. Among them, Na with NASICON structure a M b (PO 4 ) c The material has attracted extensive attention due to its excellent structural stability, thermal safety and cycle life.
[0003] NASICON type Na 3 V 2 (PO 4 ) 3 It is one of the most widely studied polyanionic compounds, with a capacity of 117.6 mAhg -1 The theoretical capacity of 2.5V is 1.3V, showing excellent cycle stability and a high discharge voltage of 3.4V. However, expensive and toxic vanadium resources may limit its widespread application. In 2016, Goodenough's group first reported a compound Na2O3 obtained by replacing part of vanadium with cheap and environmentally friendly manganese. 4 MnV(PO 4 ) 3 . 4 MnV(PO 4 ) 3 / C positive electrode at 3.6V and 3.3V for Na + / Na presents two voltage platforms, corresponding to Mn 3+ / Mn 2+ and V4 + / V 3+ Redox couple. Higher average operating voltage and lower cost make Na 4 MnV(PO 4 ) 3 / C has become an attractive cathode material for sodium-ion batteries. 4 MnV(PO 4 ) 3 The application of Na / C positive electrode also faces two challenges: 1) 4 MnV(PO 4 ) 3 / C, like most polyanionic materials, has poor intrinsic electronic conductivity, which limits its rate performance. 2) Mn 3+ The Jahn-Teller distortion may lead to structural instability during the cycling process.
[0004] Traditionally, superconducting carbon coating, cation substitution, and particle nano-sizing have been used to overcome the above shortcomings. Reduced graphene oxide (rGO) and carbon nanotubes (CNTs) have been widely used to improve Na 4 MnV(PO 4 ) 3 / C electronic conductivity. Most reported Na 4 MnV(PO 4 ) 3 / C cathodes are used with high content of carbon nanotubes or rGO, which increases the cost and also leads to lower packing density. High performance Na 4 MnV(PO 4 ) 3 / C positive electrode materials are more attractive.
[0005] Foreign ion doping or substitution strategies have been widely used to enhance the structural / chemical stability of various cathode materials or to promote electron and ion transport. In order to suppress Jahn-Teller distortion, the use of Mg 2+ 、Al 3+ Cr 3+ 、Ce 3+ and Cu 2+ To Na 4 MnV(PO 4 ) 3 All of these cation-substituted materials exhibit enhanced cycling stability due to the partial replacement of Mn with inactive cations. 2+ The lattice distortion can be effectively suppressed. In addition, these alternative cations provide additional positive effects. Ghosh S. et al. studied the Na x V N 0.75 M 0.25 (PO 4 ) 3 (M = Mg and Al) cathode. In addition to suppressing the Jahn-Teller effect, it also shows that Al in the Al-NMVP cathode 3+ The generated Na + Vacancies enhance the sodium ion transfer kinetics, resulting in a discharge capacity of more than 80 mAh g at 5C rate. -1 Lavela P et al. reported that partial substitution of Mn with Cr provides a strong and flexible framework with improved sodium diffusivity.3.2 Mn 0.2 Cr 0.8 V(PO4) 3 / C provides 65.3mAhg at 5C rate -1 Wang et al. found that Ce 3+ Doped with Na 4 MnV(PO 4 ) 3 / C crystal framework can greatly improve electron transfer and promote Na + diffuses and stabilizes the crystal structure. As a result, the optimal Na 4 Mn 0.9 Ce 0.1 V(PO 4 ) 3 @CeO 2 / C exhibits excellent electrochemical performance (50.3 mAhg-1 at 50C). Soundharrajan V. et al. reported a cotton candy-like Cu-doped NVMCP with excellent rate performance (68 mAhg-1 at 40C) and good cycling stability. First-principles calculations confirmed that Cu doping enhances conductivity and promotes fast electron transport. In addition to reports on the substitution of Mn sites, partial substitution of vanadium content has also been reported as an effective strategy to improve electrochemical performance. Xu C. et al. used Al 3+ Replace V 3 + , the obtained Na 4 V 0.8 Al 0.2 Mn(PO 4 ) 3 Showing favorable Na + Kinetic and structural stability, discharge capacity at 40C is about 84mAhg -1 They pointed out that the strong Al-O bonds with enhanced ionic covalent character greatly alleviated the structural deformation of NMVP and reduced the dissolution of Mn ions.
[0006] Combining the results of all the above reports, we can conclude that high performance modified Na 4 MnV(PO 4 ) 3 / C materials should have high electron and Na + The optimal substitution element M should 1) have a strong MO bond to stabilize the crystal structure, 2) be a high-valent cation that can provide sodium ion vacancies to enhance Na + mobility, 3) can improve the intrinsic electronic conductivity. As far as we know, Zr 4+ With high Zr-O bond energy (△H Zr-O=766.1±10.6 kJmol -1 >△H V-O =637 kJmol -1 >△H Mn-O =362±25 kJmol -1 ) and high valence (+4) and large ionic radius (Zr 4+ (0.72Å), larger than Mn 2+ (0.67Å) and V 3+ (0.64Å)). It may be a good candidate for tuning the structure and performance of NMVP. It is reasonable to assume that the strong Zr-O bonds can stabilize the framework structure during long-term cycling and the large size of Zr 4+ The expanded lattice structure can provide a wide Na + In addition, the use of high-priced Zr 4+ Replacement of Mn 2+ Can produce Na + Mobility of sodium ion vacancies.
[0007] At present, there have been studies that have begun to dope zirconium with Na 4 Mn V (PO 4 ) 3 / C materials doped with V to improve the performance of the materials, and began to conduct research and patent layout. For example, Guanglie Cui's research group reported a Na 3.8 MnV 0.8 Zr 0.2 (PO 4 ) 3 Sodium ion positive electrode material, but did not explore the effect of V doping content on battery performance. Patent document CN116826008A also discloses a transition metal vanadium-doped Na 4-x N x V 1-y M y Mn(PO 4 ) 3 For the positive electrode material of sodium ion battery, N can be Zr, where 0<x≤0.5, 0<y≤0.5. There is also no effect of the doping content of vanadium-doped elements on the performance of electrode materials. It can be seen that although the V-doping of Zr in sodium vanadium manganese phosphate has begun to improve the performance of electrode materials, the Zr doping of these materials is at a low level, and the effect of high V-doping of Zr on the material has not been studied, and the effect of the amount of Zr doping on the electrochemical performance of the material has not been considered. Summary of the invention
[0008] In view of the shortcomings of the prior art, the present application provides a Na 4-x V1-x Mn x (PO 4 ) 3 @C composite material, the electrochemical properties of sodium vanadium manganese phosphate are enhanced by regulating the content of V-position doping with carbon coating and transition metal elements. The material has excellent electrochemical properties, including high rate performance and long cycle life.
[0009] In order to achieve the above object, the present invention adopts the following technical solution: A transition metal-doped sodium manganese vanadium phosphate composite material, the composite material having the following structural formula: Na 4- x V 1-x Mn x (PO 4 ) 3 @C, wherein 0.8≤x≤1, M is a 4d transition metal, characterized in that the composite material is spherical, the composite nanomaterial has a core-shell structure, including a core and a shell layer coated on the surface of the core, and the core is Na 4-x V 1- x Mn x (PO 4 ) 3 Spherical particles, the shell is coated with the Na 4-x V 1-x Mn x (PO 4 ) 3 Amorphous carbon layer on the surface of spherical particles.
[0010] In the preferred transition metal-doped sodium manganese vanadium phosphate composite material, M is one or more of Y, Nb, Zr, Mo, Ru, and Cd; In the preferred transition metal-doped sodium manganese vanadium phosphate composite material, M is Zr, and x=0.9; The preferred transition metal-doped sodium manganese vanadium phosphate composite material has a carbon mass ratio of 1% to 10%; The preferred transition metal-doped sodium manganese vanadium phosphate composite material has a Raman spectrum ID / IG ratio of 1-1.25, and the peak intensities of ID and / IG are around 1300 cm-1 and 1600 cm-1, respectively; The preferred transition metal-doped sodium manganese vanadium phosphate composite material D50 has a particle size range of 2um-10um.
[0011] On the other hand, the present invention also provides a preparation method of a transition metal-doped sodium manganese vanadium phosphate composite material, the specific steps of which are: (1) weighing raw materials according to the stoichiometric ratio; adding a sodium source, a phosphorus source, a manganese source, a vanadium source, and a transition metal doping source into deionized water in sequence and dissolving them completely; (2) adding a certain amount of citric acid to the solution in step 1 and stirring evenly to obtain a mixed solution; (3) placing the mixed solution obtained in step 2 in a spray drying device for spray drying to obtain a powder; (4) The powder obtained in step 3 is calcined under an inert atmosphere to obtain Na 4-x V 1-x Mn x (PO 4 ) 3 @CComposite materials.
[0012] Preferably, the sodium source, phosphorus source, manganese source, vanadium source, and transition metal doping source are soluble salts containing these elements, respectively.
[0013] The preferred spray drying temperature is 160-220°C, the calcination temperature is 500-1000°C, and the time is 5-12 hours.
[0014] The third aspect of the present invention is to provide a technical solution Na 4-x V 1-x Mn x (PO 4 ) 3 @C or Na prepared by the method described in the above technical solution 4-x V 1-x Mn x (PO 4 ) 3 @C is used as a cathode material for sodium-ion batteries.
[0015] The beneficial effects of the present invention are: (1) In the present invention, the spray drying-calcination method is used to prepare the microsphere morphology by liquid phase synthesis, which significantly increases the specific surface area of the material, promotes the contact between the electrolyte and the active material, thereby improving the capacity of the battery. The spherical secondary particles are conducive to improving the packing density of the material. In addition, the amorphous carbon coating layer effectively inhibits the dissolution of the active material and greatly improves the conductivity of the material.
[0016] (2) Na of the present invention 4-x V 1-x Mn x (PO 4 ) 3@C The problems of poor conductivity and rapid capacity decay of positive electrode materials of sodium ion batteries are solved by regulating the doping amount of vanadium doping elements. By regulating the doping amount of vanadium, the doping amount of V is maintained at a high level. At the same time, the bond energy between the metal and oxygen atoms in the material is changed by the doping amount, the lattice structure framework of the material is stabilized, and the bond energy between the metal and oxygen in the material reaches a stable state of optimal balance. Not only the electrochemical stability of the electrode material is improved, but also the performance of the electrode material under high current conditions is enhanced, ensuring the long-term cycle stability of the electrode material. At the same time, the preparation method provided by the present invention is simple and controllable, and easy to mass produce. BRIEF DESCRIPTION OF THE DRAWINGS
[0017] Figure 1 The Na prepared in Example 1 of the present invention 3.1 V 0.1 MnZr 0.9 (PO 4 ) 3 XRD pattern of @C(NMVZP@C) sample.
[0018] Figure 2 The Na prepared in Example 1 of the present invention 3.1 V 0.1 MnZr 0.9 (PO 4 ) 3 @TG spectrum of C sample.
[0019] Figure 3 The Na prepared in Example 1 of the present invention 3.1 V 0.1 MnZr 0.9 (PO 4 ) 3 @C ID / IG image of the sample.
[0020] Figure 4 The Na prepared in Example 1 of the present invention 3.1 V 0.1 MnZr 0.9 (PO 4 ) 3 XPS spectrum of @C sample.
[0021] Figure 5 The Na prepared in Example 1 of the present invention 3.1 V 0.1 MnZr 0.9 (PO 4 ) 3 @C SEM image of the sample.
[0022] Figure 6 The Na prepared in Example 1 of the present invention 3.1 V 0.1MnZr 0.9 (PO 4 ) 3 CV curve of @C sample at 0.1mv / s rate.
[0023] Figure 7 The Na prepared in Example 1 of the present invention 3.1 V 0.1 MnZr 0.9 (PO 4 ) 3 @GCD curve of C sample.
[0024] Figure 8 The Na prepared in Example 1 of the present invention 3.1 V 0.1 MnZr 0.9 (PO 4 ) 3 @C charge and discharge curves of samples at different current densities.
[0025] Fig. 9 Preparation of Na for Examples 1, 2, 3, and 4 of the present invention 3.1 V 0.1 MnZr 0.9 (PO 4 ) 3 @C, (x=1, 0.95, 0.9, 0.8) comparison of the cycle curves of samples at 1C current density.
[0026] Fig.10 The Na prepared in Example 1 of the present invention 3.1 V 0.1 MnZr 0.9 (PO 4 ) 3 Cycling curve of @C sample at 0.2C current density. DETAILED DESCRIPTION
[0027] To make the technical solutions and advantages of the present invention more clear, the present invention and its beneficial effects will be described in further detail below in conjunction with specific implementation methods and accompanying drawings, but the implementation methods of the present invention are not limited thereto.
[0028] In the present invention, "at least one" means one or more, and "plurality" means two or more. "At least one of the following" or similar expressions refers to any combination of these items, including any combination of single items or plural items. For example, "at least one of a, b, or c", or "at least one of a, b, and c", can all mean: a, b, c, ab (i.e., a and b), ac, bc, or abc, where a, b, and c can be single or multiple.
[0029] Embodiment 1: Na 3.1 V 0.1 MnZr 0.9 (PO 4 ) 3 @C The preparation method of micron ball nano material comprises the following steps: 1) Add 1 mmol of ammonium metavanadate, 10 mmol of manganese acetate tetrahydrate, 9 mmol of zirconium oxychloride octahydrate, 30 mmol of disodium hydrogen phosphate dihydrate, and 0.33 mmol of sodium citrate to 100 mL of deionized water, and stir at room temperature to completely dissolve; 2) Add 4.2 g of citric acid monohydrate to the solution obtained in 1) and continue stirring for 30 min; 3) spray drying the solution obtained in step 2) at a spray drying temperature of 160° C., a circulating gas flow of 90%, and a sampling pump of 5%. The obtained product is placed in a tubular furnace for calcination at a calcination temperature of 750° C. for 8 hours in an argon atmosphere at a heating rate of 3° C. / min. The final calcined product is Na 3.1 V 0.1 MnZr 0.9 (PO 4 ) 3 @C micron ball; The product Na 3.1 V 0.1 MnZr 0.9 (PO 4 ) 3 @C micron sphere as an example, after X-ray diffractometer determination, such as Figure 1 As shown, the X-ray diffraction pattern (XRD) shows that Na 3.1 V 0.1 MnZr 0.9 (PO 4 ) 3 @C microsphere and Na 3.1 V 0.1 MnZr 0.9 (PO 4 ) 3@C The peak positions of the microspheres are consistent, and the peak positions of the products are consistent with the JCPDS cards; Figure 2 The thermogravimetric analysis results show that within 400 ° C, Na 3.1 V 0.1 MnZr 0.9 (PO 4 ) 3 @C The mass of the micron ball has almost no loss, but as the temperature increases, the mass begins to decrease and the change is large; Figure 3 Raman test results show that Na 3.1 V 0.1 MnZr 0.9 (PO 4 ) 3 @C's ID / IG=1.002, the test result indicates Na 3.1 V 0.1 MnZr 0.9 (PO 4 ) 3 @C has good electrical conductivity.
[0030] The Na prepared by the present invention 3.1 V 0.1 MnZr 0.9 (PO 4 ) 3 @C microspheres are used as positive electrode active materials for sodium ion batteries. The preparation method is as follows: Na 3.1 V 0.1 MnZr 0.9 (PO 4 ) 3 @C micron ball is used as active material, acetylene black is used as conductive agent, PVDF is used as binder, and the mass ratio of active material, acetylene black and polytetrafluoroethylene is 70:20:10; after they are fully mixed in proportion, a small amount of NMP is added, stirred evenly, and coated on 2mm thick aluminum foil as the electrode sheet of sodium ion battery; the coated positive electrode sheet is placed in an oven at 80℃ and dried for 24 hours before use; the positive electrode sheet containing 1.0M NaPF 6 and 0.2wt.%NaClO 4 The mixed solution was used as the electrolyte, the sodium sheet was used as the negative electrode, and the GFD was used as the diaphragm. In a glove box filled with argon as a protective atmosphere, the sodium ion button battery was assembled with the 2016 positive and negative battery shells. After the electrochemical performance test like Figure 7 As shown, Na 3.1 V 0.1 MnZr 0.9 (PO 4 ) 3@C The charge and discharge curve of the micron ball material has an obvious charge and discharge platform during the charge and discharge process; like Fig. 9 As shown, Na 3+x V x MnZr 1-x (PO4)3@C(x=0,0.05,0.1,0.2) microsphere material at 1C current density, Na 3.1 V 0.1 MnZr 0.9 (PO 4 ) 3 @C micron ball has the best cycle performance. 3.1 V 0.1 MnZr 0.9 (PO 4 ) 3 @C microsphere material has a capacity of up to 83mAh / g at a current density of 1C; compared with other materials, its charge and discharge performance is the best.
[0031] like Fig.10 As shown, Na 3.1 V 0.1 MnZr 0.9 (PO 4 ) 3 @C microsphere material has a discharge capacity of 103 mAh / g at a current density of 0.2C, and can maintain 88% of its capacity after 120 cycles.
[0032] Embodiment 2: 1) Add 10 mmol of manganese acetate tetrahydrate, 10 mmol of zirconium oxychloride octahydrate, 30 mmol of disodium hydrogen phosphate dihydrate, and 4.2 g of citric acid monohydrate to 100 mL of deionized water in sequence, and stir at room temperature to completely dissolve; 2) spray drying the solution obtained in step 1), the spray drying temperature is 160°C, the circulating air flow is 90%, the sampling pump is 5%, and the obtained product is placed in a tubular furnace for calcination, the calcination temperature is 750°C, the calcination time is 8 hours, the calcination atmosphere is argon, and the heating rate is 3°C / min; the final calcined product is Na 3 MnZr(PO4) 3 @C micron ball; The product Na 3 MnZr(PO4) 3 @C microsphere material as an example; after electrochemical performance testing, Na 3 MnZr(PO4) 3 @C The capacity of the microsphere material is only 43mAh / g at a current density of 1C; at a current density of 1C, the capacity retention rate drops rapidly after cycling.
[0033] Embodiment 3: 1) Add 0.5 mmol of ammonium metavanadate, 10 mmol of manganese acetate tetrahydrate, 9.5 mmol of zirconium oxychloride octahydrate, 30 mmol of disodium hydrogen phosphate dihydrate, 0.16 mmol of sodium citrate, and 4.2 g of citric acid monohydrate to 100 mL of deionized water in sequence, and stir at room temperature to completely dissolve; 2) spray drying the solution obtained in step 1), the spray drying temperature is 160°C, the circulating air flow is 90%, the sampling pump is 5%, and the obtained product is placed in a tubular furnace for calcination, the calcination temperature is 750°C, the calcination time is 8 hours, the calcination atmosphere is argon, and the heating rate is 3°C / min; the final calcined product is Na 3.05 V 0.05 MnZr 0.95 (PO 4 ) 3 @C micron ball; The product Na 3.05 V 0.05 MnZr 0.95 (PO 4 ) 3 @C microsphere material as an example; after electrochemical performance testing, Na 3.05 V 0.05 MnZr 0.95 (PO 4 ) 3 @C microsphere material has a capacity of only 31 mAh / g at 1C current density; Embodiment 4: 1) Add 2mmol of ammonium metavanadate, 10mmol of manganese acetate tetrahydrate, 8mmol of zirconium oxychloride octahydrate, 30mmol of disodium hydrogen phosphate dihydrate, 0.66mmol of sodium citrate, and 4.2g of citric acid monohydrate to 100mL of deionized water in sequence, and stir at room temperature to completely dissolve; 2) spray drying the solution obtained in step 1), the spray drying temperature is 160°C, the circulating air flow is 90%, the sampling pump is 5%, and the obtained product is placed in a tubular furnace for calcination, the calcination temperature is 750°C, the calcination time is 8 hours, the calcination atmosphere is argon, and the heating rate is 3°C / min; the final calcined product is Na 3.2 V 0.2 MnZr 0.8 (PO 4 ) 3 @C micron ball; The product Na 3.2 V 0.2 MnZr 0.8 (PO 4 ) 3@C microsphere material as an example; after electrochemical performance testing, Na 3.2 V 0.2 MnZr 0.8 (PO 4 ) 3 @C microsphere material has a capacity of only 58 mAh / g at 1C current density; for Na 3.2 V 0.2 MnZr 0.8 (PO 4 ) 3 @C microsphere material, at 1C current density, the capacity retention rate after cycling is poor.
[0034] By comparing the experimental data of files 1-4, we can see that the change of Zr doping content affects the stability of the lattice structure formed in the material. When the molar ratio of Zr to V is 9:1, that is, x=0.9, the battery has the best discharge capacity and cycle performance. At this time, more Zr-O bonds in the material can stabilize the framework structure of the material during long-term cycles. At the same time, large-size Zr 4+ The expanded lattice structure can provide a wide Na + However, if the Zr content is greater than 0.9 or less than 0.9, the capacity of these positive electrode materials is poor, and the capacity retention rate after cycling is also poor. It can be seen that the lattice in the material cannot reach a stable structure at this time, resulting in the degradation of the electrochemical properties of the material.
[0035] According to the disclosure and teaching of the above description, those skilled in the art to which the present invention belongs can also change and modify the above embodiment. Therefore, the present invention is not limited to the above specific embodiment, and any obvious improvement, replacement or modification made by those skilled in the art on the basis of the present invention belongs to the protection scope of the present invention. In addition, although some specific terms are used in this specification, these terms are only for the convenience of description and do not constitute any limitation to the present invention.
Claims
1. A transition metal-doped sodium manganese vanadium phosphate composite material, the composite material having the following structural formula: Na 4-x V 1- x Mn x (PO4)3@C, wherein 0.8≤x≤1, M is a 4d transition metal, characterized in that The composite material is spherical, and the composite nanomaterial has a core-shell structure, including a core and a shell layer coated on the surface of the core, wherein the core is Na 4-x V 1-x Mn x (PO4)3 spherical particles, the shell is coated on the Na 4-x V 1-x Mn x Amorphous carbon layer on the surface of (PO4)3 spherical particles.
2. The nanocomposite material according to claim 1, characterized in that In the composite material, M is one or more of Y, Nb, Zr, Mo, Ru, and Cd, and preferably M is Zr.
3. The nanocomposite material according to claim 2, characterized in that The composite material has x=0.
9.
4. The nanocomposite material according to claim 1, characterized in that The carbon mass ratio in the composite material is 1%-10%.
5. The nanocomposite material according to claim 1, characterized in that: The ratio of Raman spectrum ID / IG in the composite material is 1-1.25, and ID and / IG are 1300 cm -1 and 1600cm -1 The peak intensity near .
6. The nanocomposite material according to claim 1, characterized in that The D50 particle size range of the composite material is 2um-10um.
7. A method for preparing the transition metal-doped sodium manganese vanadium phosphate composite material according to any one of claims 1 to 6, characterized in that: The specific preparation steps are: (1) weighing raw materials according to the stoichiometric ratio; adding a sodium source, a phosphorus source, a manganese source, a vanadium source, and a transition metal doping source into deionized water in sequence and dissolving them completely; (2) adding a certain amount of citric acid to the solution in step 1 and stirring evenly to obtain a mixed solution; (3) placing the mixed solution obtained in step 2 in a spray drying device for spray drying to obtain a powder; (4) The powder obtained in step 3 is calcined under an inert atmosphere to obtain Na 4-x V 1-x Mn x (PO4)3@C composite materials.
8. The preparation method according to claim 7, characterized in that: The sodium source, phosphorus source, manganese source, vanadium source and transition metal doping source are soluble salts containing these elements respectively.
9. The preparation method according to claim 7, characterized in that: The spray drying temperature is 160-220°C, the calcination temperature is 500-1000°C, and the time is 5-12h.
10. Use of the nanocomposite material according to claims 1-6 or the nanocomposite material prepared by the method according to claims 7-9 in sodium ion batteries.
Citation Information
Patent Citations
4d transition metal doped and modified vanadium manganese sodium phosphate positive electrode material and preparation method thereof
CN116826008A
Cited By
Carbon-coated manganese vanadium ruthenium sodium phosphate positive electrode material as well as preparation method and application thereof
CN121282182A